Novel P, P-diphenylphosphinic amide-TEMPO radicals family: Synthesis, crystal structures, spectroscopic characterization, magnetic properties and DFT calculations. (1st April 2018) - G. Reis, Samira; del Águila-Sánchez, Miguel A.; P. Guedes, Guilherme; Navarro, Yolanda; A. Allão Cassaro, Rafael; B. Ferreiraa, Glaucio; Calancea, Sergiu; López-Ortiz, Fernando; G. F. Vaz, Maria
Graphical abstract: Three new radicals (C6 H5 )2 P(X )-NH-TEMPO, (X = O, S, Se) were synthesized and their structure, magnetic properties, electronic structure and charge distribution analysed. Abstract: A new family of three P, P -diphenylphosphinic amide-TEMPO radicals with general formula (C6 H5 )2 P(X )-NH-TEMPO, X = O (1 ), S (2 ) and Se (3 ) were obtained by reaction of chlorodiphenylphosphine with 4-amino-2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical (NH2 -TEMPO) and subsequent oxidation with H2 O2 and elemental sulfur or selenium. These radicals were characterized by UV–Vis, FT-IR and 1 H, 31 P and 77 Se nuclear magnetic resonance spectroscopy. The crystal structures of all radicals were determined by single-crystal X-ray diffraction. The magnetic study of all diphenylphosphinic amide-TEMPO radicals reveals very weak intermolecular ferromagnetic interactions. Density functional theory (DFT) calculations have been also performed to support the interpretation of magnetic properties and electronic structure.